La politización de lo sagrado en la comunidad española de Buenos Aires: Actos, misas y ‘platos únicos’ a favor del franquismo durante la Guerra Civil (1936-1939) - Ferreyra, Alejandra Noemi (2022)
The Spanish Civil War (1936-1939) generated multiple propaganda and solidarity campaigns in over the argentinian territory, but that especially involved the community of Spanish immigrants that live in Buenos Aires. The public acts became a central element to motivate solidarity and to bring together new adherents. This paper aims to analyze the acts (masses and "uniques dishes") made by the sector of the Spanish community in Buenos Aires that demonstrated in favor of Francoism in Spain during the war. In particular, it is expected to examine the interaction of religious and political elements that happened in some of the public acts organized by supporters of the Franco’s regime in Buenos Aires, as well as their evolution as the conflict unfolds and prefigures a scene of military victory in the peninsula. In this particular case, it is studied what was the role of the Argentine State in front of this active pro-Franco mobilization that was generated in the public sphere during the civil war.